Speaking Skills of EFL Student of STKIP Al Maksum: Problems and Strategies - Marsika Sepyanda; Muhammad Hasan (The Seall Journal, 2023)
The purposes of this study were to find out the problems faced by the student teachers of STKIP Al Maksum in speaking English and to find out the strategies used by the lecturers of STKIP Al Maksum to cope with the problems. A case study was used, and purposeful sampling was utilized. The interview was used to find out the student teachers’ problems in speaking English. Interviews and documentation were used to find out the lecturer’s strategies to cope with the problems. The problems and the strategies were: 1) lack of vocabulary mastery, to cope with the problem, the lecturer kept the student teachers on speaking the target language; 2) lack of grammar mastery and the strategy was the lecturer provided oral feedback to the student teachers’ grammar used; 3) lack of pronunciation, in order to cope with the problem, the lecturer provided some speaking activities and oral feedback; 4) anxiety-provoking situation, to deal with the problem, the lecturer used small groups, promoted equal participation after giving preparation time, and gave positive feedback; 5) lack of self-confidence, to deal with the problems, the lecturer applied small groups discussion, gave them the equal opportunity to speak after giving preparation time, and enforced repetition; 6) the interference of the mother tongue, in order to cope with the problem, the lecturer applied some speaking activities and encouraged them to speak the target language.